2023
DOI: 10.1111/1471-0528.17558
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with advanced ovarian cancer after primary debulking surgery versus neoadjuvant chemotherapy: Results from the randomised SCORPION trial (NCT01461850)

Abstract: ObjectiveTo investigate the effect of treatment with neoadjuvant chemotherapy (NACT) followed by interval debulking surgery (IDS), versus primary debulking surgery (PDS), on quality of life (QoL) in patients with advanced epithelial ovarian cancer (EOC).DesignRandomised trial conducted in a single institution.SettingDivision of Gynaecologic Oncology, Fondazione Policlinico Universitario A. Gemelli IRCCS, Rome, Italy.SamplePatients with stage‐IIIC/IV EOC and high tumour load.MethodsPatients were randomised (1:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In the current paper, we aimed to analyse the possible correlations between preoperative levels of CA125, preoperative systemic inflammation, the extent of the disease and long-term outcomes of advanced-stage ovarian cancer. As mentioned before, the levels of CA125 cannot be considered as a gold standard in order to identify ovarian cancer patients and to predict long-term outcomes [4][5][6]; therefore, attention was focused on identifying other prognostic markers which might provide an adequate identification of cases who could benefit most from debulking surgery followed by adjuvant chemotherapy or, oppositely, who could better benefit from neoadjuvant therapy followed be interval debulking surgery [10][11][12]. One of the most commonly cited prognostic factors which has been recently investigated in patients suffering from malignant diseases is represented by the inflammatory status of each patient.…”
Section: Discussionmentioning
confidence: 99%
“…In the current paper, we aimed to analyse the possible correlations between preoperative levels of CA125, preoperative systemic inflammation, the extent of the disease and long-term outcomes of advanced-stage ovarian cancer. As mentioned before, the levels of CA125 cannot be considered as a gold standard in order to identify ovarian cancer patients and to predict long-term outcomes [4][5][6]; therefore, attention was focused on identifying other prognostic markers which might provide an adequate identification of cases who could benefit most from debulking surgery followed by adjuvant chemotherapy or, oppositely, who could better benefit from neoadjuvant therapy followed be interval debulking surgery [10][11][12]. One of the most commonly cited prognostic factors which has been recently investigated in patients suffering from malignant diseases is represented by the inflammatory status of each patient.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Vizzielli et al calculated a simple adjusted laparoscopic score to predict major postoperative complications after PDS, which could help surgeons adopt tailored strategies on an individual basis (17). In addition, a number of randomized trials which compared survival outcomes of neoadjuvant chemotherapy (NACT) and PDS suggested that survival outcomes in neoadjuvant chemotherapy followed by interval debulking surgery (IDS) was not inferior to PDS followed by chemotherapy with no significant difference in global quality-of-life (QoL) (18)(19)(20)(21). Considering these findings, NACT or PDS should be carefully selected, and maximal effort at performing cytoreduction both in the intrathoracic and abdominopelvic tract may improve survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the primary surgery group there was a significantly higher likelihood of bowel resection, stoma, post operative complications and prolonged hospital stay. Since any of these can impact short‐ and long‐term quality of life, they must be taken into consideration when planning treatment (3). In a similar vein, Van Oudhesen et al investigated the efficacy of a laparoscopic sacrocolpopexy versus vaginal sacrospinous fixation for vaginal vault prolapse and showed that both are effective treatments for up to 12 months post‐surgery.…”
mentioning
confidence: 99%